An azaspirane derivative suppresses growth and induces apoptosis of ER-positive and ER-negative breast cancer cells through the modulation of JAK2/STAT3 signaling pathway - Sulaiman, N.; Mohan, C.; Basappa, B.; Pandey, V.; Rangappa, S.; Bharathkumar, H.; Kumar, Alan Prem; Lobie, P.; Rangappa, K. (Spandidos Publications, 2016)
Persistent activation of signal transducer and activator of transcription 3 (STAT3) is associated with the progression of a range of tumors. In this report, we present the anticancer activity of 2-(1-(4-(2-cyanophenyl)1-benzyl1H-indol-3-yl)-5- (4-methoxy-phenyl)-1-oxa-3-azaspiro(5,5)undecane (CIMO) against breast cancer cells. We observed that CIMO suppresses the proliferation of both estrogen receptor-negative (ER-) (BT-549, MDA-MB231) and estrogen receptor-positive (ER+) (MCF-7, and BT-474) breast cancer (BC) cells with IC50 of 3.05, 3.41, 4.12 and 4.19 M, respectively, and without significantly affecting the viability of normal cells. CIMO was observed to mediate its anti-proliferative effect in ER- BC cells by inhibiting the phosphorylation of JAK2 and STAT3 proteins. Quantitative PCR analysis demonstrated that CIMO decreases the relative mRNA expression of genes that are involved in cell cycle progression (CCND1) and cell survival (BCL2, BCL-xL, BAD, CASP 3/7/9, and TP53). In addition CIMO was observed to arrest BC cells at G0/G1 phase and of the cell cycle. Furthermore, CIMO suppressed BC cell migration and invasion with concordant regulation of genes involved in epithelial to mesechymal transition (CDH1, CDH2, OCLN and VIM). Thus, we report the utility of a synthetic azaspirane which targets the JAK-STAT pathway in ER- BC.